TINDAK TUTUR DIREKTIF DOSEN DAN MAHASISWA GEN-Z DALAM GRUP WHATSAPP KELAS PBSI C 2020 - Dwi Munja Rafikha Putri; Resdianto Permata Raharjo; Titik Indarti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
The purpose of this study is to describe the directive speech acts contained in the lecturer's conversation with generation z. Searle (in Manaf, N, A, 2011: 212) suggests that directive speech is a speech act performed by the speaker to the speech partner in order to carry out what is said. The reason behind this research is because of the fast-paced development of technology and generation z which is more adaptive to the digital world, thus enabling the influence of social life in speech acts. The research method used is the listening method with the free-involved-capable (SBLC) technique, this study uses a qualitative approach with the type of microethnigraphy research where the researcher will examine a habit in a mini group. The instrument of data research is the researcher, where the researcher serves as an observer. The data sources used were lecturers and students of gen z class PC 20, while the data collection techniques were observation, recording, and taking notes. Then the data were analyzed by transcribing the data that had been obtained and describing the data, then the researcher concluded and presented the data in written form. The results showed that there were 16 directive speech acts of gen z lecturers and students in the whatsapp group. The directive speech acts include: 1. There is one directive speech act begging (beg); 2. There are two directive speech acts pleading strongly (bid); 3. There are two directive speech acts asking (ask); 4. There are six directive speech acts asking (request); 5. There are two commanding directive speech acts; and 6. There are three directive speech acts demanding (demand). Keywords: directive speech act, whatsapp group, gen-z students